Approaches for the development of potential dengue inhibitors. Issue 15 (2nd August 2020) - Gupta, Princy; Mahajan, Aman
Abstract: Dengue is the most severe mosquito borne viral disease for several decades in tropical and subtropical countries. Dengue virus (DENV) is a part of the Flaviviridae family with single positive stranded RNA genetic material encoding a single polyprotein, which is cleaved into structural and nonstructural proteins. Lethal consequences of DENV infections range from fever to hemorrhagic manifestations, volume depletion. Until now, no strategies are accessible for specific therapeutic measures for dengue fever, although it is the most rapidly spreading mosquito-borne viral infection in the world. Global disease burden caused by DENV infections is considerable, as neither specific antiviral drugs nor vaccines exist. The present synthetic literature provides interesting information in order to design novel drugs that mostly target viral processes. This review article reviews potential anti-dengue activities possessed by synthetic and plant based molecules. Graphical Abstract: